Strategi Komunikasi Organisasi dalam Meningkatkan Etos Kerja Pegawai Kantor Camat Tungkal Jaya Kabupaten Musi Banyuasin - Santi Handa Astuti; Dalinur M Nur; Candra Darmawan (Program Studi Komunikasi dan Penyiaran Islam UIN Raden Fatah Palembang, 2019)
This research was conducted to explain the organizational communication strategy used by the Camat in increasing employee motivation. The author limits the problem that is only examines the Organizational Communication Strategy in the form of vertical communication. Therefore, this study aims to see how the Organizational Communication Strategy in Increasing Work Motivation of Employees of Tungkal Jaya Sub-District Office in Musi Banyuasin District. The data collection techniques that I use are through observation, interviews, and documentation. Interviews conducted with organizational leaders, namely the Camat, Camat Secretary and Section Head of Tungkal Jaya Sub-District Office. Data analysis method uses qualitative descriptive, based on existing assessment indicators, the organizational communication strategy in increasing employee motivation through the determination of objectives by implementing the vision and mission that must be achieved and implemented. This can be seen through the Camat leadership indicator in using Persuasive and Communicative techniques, Facility techniques, Exemplary and Service techniques.